2017
DOI: 10.1080/09168451.2017.1385381
|View full text |Cite
|
Sign up to set email alerts
|

Stereochemical assignment of the unique electron acceptor 5′-hydroxyphylloquinone, a polar analog of vitamin K1 in photosystem I

Abstract: A unique electron-accepting analog of vitamin K found in photosystem I in several species of oxygenic photosynthetic microorganisms was confirmed to be 5'-hydroxyphylloquinone (1) through stereo-uncontrolled synthesis. Furthermore, the stereochemistry of 1 obtained from Synechococcus sp. PCC 7942 was assigned to be 5'S using proline-catalyzed stereocontrolled reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…However, the biochemical synthesis pathway in vivo in photosynthetic organisms is still not completely clear. 24 In this work, the tested vitamin K isoforms displayed different potency on the reduction of the neutral lipid reservoirs in the zebrafish model, and this lipid reducing activity of the vitamin K1-analogue was reported for the first time. To the best of our knowledge, this is the first report assessing the potential of OH-PhQ on any bioactivity not related to photosynthetic functions.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…However, the biochemical synthesis pathway in vivo in photosynthetic organisms is still not completely clear. 24 In this work, the tested vitamin K isoforms displayed different potency on the reduction of the neutral lipid reservoirs in the zebrafish model, and this lipid reducing activity of the vitamin K1-analogue was reported for the first time. To the best of our knowledge, this is the first report assessing the potential of OH-PhQ on any bioactivity not related to photosynthetic functions.…”
Section: Discussionmentioning
confidence: 75%
“…Stereoisomeric mixtures and asymmetric synthesis were used to aid the stereochemical assignment of the hydroxy group at C-5 1 ′ position. 24 The elucidation of the 5′ S -OH conformation was successful, however the stereochemistry of the groups at positions C-7′ and C-11′ was assumed to be the same as from the natural K1 vitamin, meaning that the hydroxy group protons have an α orientation and the carbons R conformation. The ROESY correlations allowed the confirmation of the 5′ S -OH designation, which revealed that the hydroxy group was on the same side of the molecule plane as the carbons at C-1′ and C-2′ positions and on the opposite position of C-7 1 ′ (App.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation